The Impact of the Investors in People Standard on People Management Practices and Firm Performance - Bourne, Mike; Franco-Santos, Monica; Pavlov, Andrey; Lucianetti, Lorenzo; Martinez, Veronica; Mura, Matteo (Cranfield University, 2008)
This document reports on an extensive study into the impact of the Investors in People Standard on business performance. We started by reviewing what is already known about the Standard’s impact on business performance, before building a framework of the expected benefits of IIP from the Strategic Human Resource Management literature. This framework was tested using case studies, a survey and financial analysis to create a body of knowledge that improves our understanding of how the Investors in People Standard improves business performanc